Dynamic strength enhancement and strain rate sensitivity in ice-templated ceramics processed with and without anisometric particles. (September 2018) - Ghosh, Dipankar; Banda, Mahesh; John, James E.; Terrones, Diego A.
Abstract: We investigated the effects of platelets and strain rate on the compressive response of ice-templated porous alumina, processed from ultrafine, equiaxed particles and from a mixture of ultrafine, equiaxed and large platelet particles. Results revealed a remarkable enhancement of the quasistatic and dynamic compressive mechanical properties of the templated ceramics in the presence of platelets. Specific compressive mechanical properties of the ice-templated alumina containing platelets are superior in comparison to those of the various metallic, syntactic and natural cellular solids. In the presence of platelets, compressive strength exhibited contrasting strain rate sensitivity between the elastic and inelastic stages of deformation. Graphical abstract: Unlabelled Image